Fungal Infections in Kidney Transplant Recipients: A Comprehensive Narrative Review - Maria Mazzitelli; Federico Nalesso; Alberto Enrico Maraolo; Vincenzo Scaglione; Lucrezia Furian; Annamaria Cattelan (Microorganisms)
Background: Despite kidney transplantation being a life-saving procedure, patients experience a high risk of developing fungal infections (FIs), with an increased risk of both morbidity and mortality, especially during the first year after transplant. Methods: We herein conducted a narrative review of the most common FIs in kidney transplant recipients (KTRs), with a focus on prevalence, risk factors, mortality, and prevention strategies. Results: The most common fungal pathogens in KTRs include Candida species (up to 70% of the overall FIs), Aspergillus species, Pneumocystis jiroveci, and Cryptococcus species. Fungal colonization, diabetes mellitus, chronic liver disease, malnutrition, and pre-existing lung conditions should all be acknowledged as possible predisposing risk factors. The mortality rate can vary from 25 to 50% and according to different settings and the types of FIs. Preventive strategies are critical for reducing the incidence of FIs in this population. These include antifungal prophylaxis, environmental precautions, and infection control measures. The use of novel tools (such as PCR-based molecular assays and NGS) for rapid and accurate diagnosis may play an important role. Conclusions: Early recognition, the appropriate use of antifungal therapy, and preventive strategies are essential for improving graft loss and fatal outcomes in this vulnerable population. Future research is needed to optimize diagnostic tools, identify novel antifungal agents, and develop better prophylactic strategies for high-risk transplant recipients.